Implementation of the Independent College KIP Policy at Tanjungpura University - Azzahrawani, Nurul Rushafah; Arkanudin; Alamri, Annisa Rizqa; Adha, Nurul; Nuari, Ovie Laura; Heronimus , Viktorius (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to determine the implementation and benefits of the Smart Indonesia Card (KIP) Kuliah Merdeka program policy. The model used in this research is the Success model from Ripley and Franklin, namely (1) level of compliance, (2) continuity of implementation, and (3) performance and impact. The method used in this research is descriptive qualitative with interviews and statistical data analysis with key informants from the Academic and Student Affairs Bureau. The results of the study show that the implementation of the Independent College Smart Indonesia Card (KIP) program has been going well since the program was first proposed to potential recipients of education assistance. Utilizing this program is considered very useful, especially in the field of education. Especially for people who are still unable to meet their needs. The Academic and Student Affairs Bureau has also carried out the process and provided transparent assistance. This shows a commitment to supporting the implementation of the KIP Kuliah Merdeka program.